Effects of reforms and supervisory organizations: Evidence from the Ottoman Empire and the Istanbul bourse - Elmas Yaldiz Hanedar; Avni Önder Hanedar; Ferdi Çelikay (European Historical Economics Society (EHES), 2017)
Inefficiencies in fiscal and monetary systems of the Ottoman Empire led to higher debt burden over time and the bankruptcy for the Ottoman state in 1875. To deal with these inefficiencies, reforms were implemented, as supervisory organizations were established during the default period. We ask how investors traded at the Istanbul bourse evaluated the outcomes of these reforms and organizations. We manually collect data on price of the General Debt bond from 1873 to 1883. Using the GARCH methodology, we examine the volatility jumps in return of the bond due to the reforms and supervisory organization in the Ottoman Empire. The volatility changes are indicators for risk perceptions of the investors. Our empirical results support that investors positively responded to foundation of the Ottoman Public Debt Administration and the acceptance of gold standard, heralding the persistent decrease in the risk premia over time. The Ottoman case is instructive for the understanding of today's economic situation in emerging markets such as Greece, while we could argue that long-lived and comprehensive measures with foreign creditors' supervision on fiscal and monetary systems matter more for investors' perceptions. No empirical research studies the impacts of the reforms and supervisory organizations on the Istanbul bourse, as this large dataset has never been used before.
Keywords: G1; N25; N45; 330; Reforms; Financial control organizations; Moratorium; the Istanbul bourse; Crises; GARCH